PRODUCTIVE MANAGEMENT OF ZAKAT FUNDS FOR MUSTAHIQ EMPOWERMENT AT THE ORPHAN FRIEND DORMITORY IN MEDAN CITY - Lubis, Rofifah Abiyyah; Sazali, Hasan (istinbath, 2024)
This research aims to determine how to manage productive zakat funds to empower mustahik in the Sahabat Yatim Dormitory. This research focuses on how zakat funds are collected, allocated and utilized to improve the welfare of mustahik, especially orphans and poor people. Management of productive Zakat funds for the empowerment of Mustahik Sahabat Yatim is an effort to enhance the welfare of underprivileged communities, especially abandoned orphans who are unable and can be used for educational and future needs. The research method is descriptive qualitative and uses observation, interviews and documentation. This analysis technique uses three inductive data analysis processes: processing data, presenting data, and drawing conclusions. The results of this research show that productive management of Zakat funds in Sahabat Yatim can encourage inclusive economic growth and provide a sustainable positive impact on society. It also provides an important contribution to the practical and theoretical understanding of the role of productive zakat in empowering mustahik, especially for orphans.